prove that. tan 3x ×tan 2x ×tan x =tan3x - tan 2x - tan x
Answers
Answered by
20
hello... ☺
let
3x = 2x➕ x
take tan on both side
tan3x = tan (2x➕x)
tan3x = (tan2x➕tanx)➗1➖tan2x tanx
(1➖tan2x tanx)tan3x = tan2x➕tanx
tan3x ➖tanx tan2x tan3x = tan2x➖tanx
tanx tan2x tan3x = tan3x➖tan2x➖tanx
hence proved!!!
thank you ☺
let
3x = 2x➕ x
take tan on both side
tan3x = tan (2x➕x)
tan3x = (tan2x➕tanx)➗1➖tan2x tanx
(1➖tan2x tanx)tan3x = tan2x➕tanx
tan3x ➖tanx tan2x tan3x = tan2x➖tanx
tanx tan2x tan3x = tan3x➖tan2x➖tanx
hence proved!!!
thank you ☺
aadi55:
thx buddy
Answered by
14
We know that,
![3x = 2x + x 3x = 2x + x](https://tex.z-dn.net/?f=3x+%3D+2x+%2B+x)
Taking tan on both sides
![\tan(3x) = \tan(2x + x) \tan(3x) = \tan(2x + x)](https://tex.z-dn.net/?f=+%5Ctan%283x%29+%3D+%5Ctan%282x+%2B+x%29+)
By using identity of tan. i.e.,
![\tan(x + y) = \frac{ \tan(x) + \tan(y) }{1 - \tan( x ) \tan(y) }\\ \tan(x + y) = \frac{ \tan(x) + \tan(y) }{1 - \tan( x ) \tan(y) }\\](https://tex.z-dn.net/?f=+%5Ctan%28x+%2B+y%29+%3D+%5Cfrac%7B+%5Ctan%28x%29+%2B+%5Ctan%28y%29+%7D%7B1+-+%5Ctan%28+x+%29+%5Ctan%28y%29+%7D%5C%5C+)
We get
![\tan(3x) = \frac{ \tan(2x) + \tan(x) }{1 - \tan(2x) \tan(x) } \\ \\ on \: cross \: multiplication \\ \\ \tan(3x) - \tan(3x) \tan(2x) \tan(x) \\= \tan(2x) + \tan(x) \tan(3x) = \frac{ \tan(2x) + \tan(x) }{1 - \tan(2x) \tan(x) } \\ \\ on \: cross \: multiplication \\ \\ \tan(3x) - \tan(3x) \tan(2x) \tan(x) \\= \tan(2x) + \tan(x)](https://tex.z-dn.net/?f=+%5Ctan%283x%29+%3D+%5Cfrac%7B+%5Ctan%282x%29+%2B+%5Ctan%28x%29+%7D%7B1+-+%5Ctan%282x%29+%5Ctan%28x%29+%7D+%5C%5C+%5C%5C+on+%5C%3A+cross+%5C%3A+multiplication+%5C%5C+%5C%5C+%5Ctan%283x%29+-+%5Ctan%283x%29+%5Ctan%282x%29+%5Ctan%28x%29+%5C%5C%3D+%5Ctan%282x%29+%2B+%5Ctan%28x%29+)
![\tan(3x) \tan(2x) \tan(x) \\= \tan(3x) - \tan(2x) - \tan(x) \tan(3x) \tan(2x) \tan(x) \\= \tan(3x) - \tan(2x) - \tan(x)](https://tex.z-dn.net/?f=+%5Ctan%283x%29+%5Ctan%282x%29+%5Ctan%28x%29+%5C%5C%3D+%5Ctan%283x%29+-+%5Ctan%282x%29+-+%5Ctan%28x%29+)
⭐HOPE IT MAY HELP YOU⭐
Taking tan on both sides
By using identity of tan. i.e.,
We get
⭐HOPE IT MAY HELP YOU⭐
Similar questions